2003
DOI: 10.1007/bf03033734
|View full text |Cite
|
Sign up to set email alerts
|

Influence of obesity on lymph node recovery from rectal resection specimens

Abstract: Careful lymph node dissection from colorectal resection specimens is important procedure for cancer staging. Present study intended to assess the impact of surgical technique and patient's obesity on this process. Number of lymph nodes harvested by manual dissection from resection specimens of 141 patients with rectal cancer and the rate of nodal metastases were analyzed and compared in different groups of patients selected by length of resection specimen and body mass index. The median and mean number of lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(30 citation statements)
references
References 16 publications
1
28
1
Order By: Relevance
“…11 Görög et al demonstrated that a most significant reduction in the mean number of lymph nodes was observed in obese patients and that this subset of patients presented the lowest rate of nodal metastases. 17 In this series, the same proportion of obese patients was observed in both groups.…”
Section: Discussionsupporting
confidence: 56%
“…11 Görög et al demonstrated that a most significant reduction in the mean number of lymph nodes was observed in obese patients and that this subset of patients presented the lowest rate of nodal metastases. 17 In this series, the same proportion of obese patients was observed in both groups.…”
Section: Discussionsupporting
confidence: 56%
“…It remains unknown why age and gender were related to the NLNR as shown not only in the present but also in other studies (2,3,10). Studies have reported that the NLNR is influenced also by inflammation (21), diverticulum (21) and obesity (19,23,24). In this manner, the NLNR is determined most prominently by the extent of surgery, but is influenced to some degree by other factors.…”
Section: Discussionmentioning
confidence: 57%
“…This neoadjuvant therapy has been shown to result in a significant decrease in both the size and number of LNs available for examination after resection [29,35] . In addition, older age and obesity may reduce the number of LNs retrieved [29,32,36] . Also, the number of LNs that can be retrieved may also depend on the immune response of a patient as the size and morphology of LNs are modified by immune responses [37,38] .…”
Section: Total Number Of Dissected Lymph Nodes and N Stagementioning
confidence: 99%